1988
DOI: 10.1302/0301-620x.70b4.3403595
|View full text |Cite
|
Sign up to set email alerts
|

Bone lengthening in rabbits by callus distraction. The role of periosteum and endosteum

Abstract: Fig. 1chanics of callotasis and to determine the role of periosteum and endosteum in callus formation. MATERIALS AND METHODSThe experimental study was carried out on 27 immature Japanese white rabbits weighing about 2.0 kg. A unilateral dynamic external fixation device (Orthofix M-100, Fig. 1) was applied to the right tibia which, in the rabbit, is fused with the fibula in its distal half. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
155
2
12

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(179 citation statements)
references
References 0 publications
10
155
2
12
Order By: Relevance
“…28 While most authors agree with the concept that distraction osteogenesis leads primarily to direct or intramembranous bone formation, [29][30][31] some studies reveal at least a temporary endochondral pathway or transchondral mechanism described most often in a rabbit or rat model. [31][32][33] Ilizarov considered cartilage formation to be an unmistakable indication of unstable fixation. However, local ischemia, due to disruption of medullary vessels during extensive distraction, may also account for the appearance of cartilaginous islands, especially in the early stages of distraction.…”
Section: Discussionmentioning
confidence: 99%
“…28 While most authors agree with the concept that distraction osteogenesis leads primarily to direct or intramembranous bone formation, [29][30][31] some studies reveal at least a temporary endochondral pathway or transchondral mechanism described most often in a rabbit or rat model. [31][32][33] Ilizarov considered cartilage formation to be an unmistakable indication of unstable fixation. However, local ischemia, due to disruption of medullary vessels during extensive distraction, may also account for the appearance of cartilaginous islands, especially in the early stages of distraction.…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of periosteum as the main source of blood supply is critical [46,[75][76][77][78][79][80][81]. Its disruption significantly decelerates bone formation [75,82].…”
Section: Osteotomy Techniques and Biology Of Callotasismentioning
confidence: 99%
“…Ilizarov and others firmly recommended corticotomies to preserve medullary blood flow [26,80,83]. However, this is difficult to perform and experimental work revealed that complete bone separation (osteotomy) is equally effective [76,82,[84][85][86][87]. Dual-energy X-ray absorptiometry (DEXA) and histomorphometrical studies showed that the periosteum produces up to five-fold more callus than bone marrow during lengthening [74,75,88,89].…”
Section: Osteotomy Techniques and Biology Of Callotasismentioning
confidence: 99%
“…Some authors have expressed concern that intramedullary nailing may compromise the endosteal blood supply of diaphyseal bone and thus affect the quality of newly formed bone during leg-lengthening procedures [8,15,18]. However, it has been shown that the periosteum and surrounding soft tissue can support osteogenesis and permit new bone formation, and it is also known these issues are particularly important for effective distraction osteogenesis [9,19,20]. In addition, Rhinelander [16] noted that reconstitution of the medullary vasculature is most likely complete within 2 weeks after reaming.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, medullary callus may contribute to vascular regeneration despite reaming, whereas plugging the canal with cement would prevent this response. Kojimoto [9] demonstrated in a rabbit model that the periosteum plays a more important role in the regeneration of distraction-callus than the endosteum.…”
Section: Discussionmentioning
confidence: 99%